PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI AKADEMIK SISWA DI INDONESIA: DATA PISA - Rokhim, Hanif Nur; Dhewantoro, Happri Novriza Setya; Suranto, Suranto (Universitas Tidar, 2024)
The study of family environment and school environment in relation to academic achievement is a topic that is often discussed. The quantitative research method in this study is secondary data analysis using data from the 2018 Program for International Student Assessment (PISA). This research was conducted in Indonesia with 8,268 respondents who filled out the questionnaire. The results of this study indicate that: (1) Family environment has a positive influence on student academic achievement. (2) Family environment has a positive influence on student academic achievement (3) Family environment and school environment together have a positive influence on student academic achievement. These findings explain that the family environment and school environment are important factors in shaping student academic achievement in Indonesia.